Analisis penanganan bullying melalui program 5S ( senyum, sapa, salam sopan, santun) di SD Muhammadiyah Pakel Program Plus - Sri Saripah Ningsih; Sugeng Riyanto (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
School culture is a behavior and way of acting that is formed automatically. Students will imitate the things around them. Both positive and negative. This study aims to : (1) describe the form of bullying behavior that occurs at SD Muhammadiyah Pakel Program Plus, (2) Describe the bullying factor, (3) describe the impact of bullying, (4) application of 5S culture, (5) Handling bullying in SD Muhammadiyah Pakel Program Plus. This research is a type of descriptive qualitative research, the subjects in this study is the principal, homeroom teacher, and students. The object of this research is the handling of bullying through the 5s program which is implemented at SD Muhammadiyah Pakel Program Plus. The data collection instruments used in this study included a grid of observation guidelines, interviews, and documentation.The results showed that the handling at SD Muhammadiyah Pakel Program Plus was that the teacher called the students involved in bullying cases, the teacher advised and approached the students, give a smile, spoke patiently, and gently, these problems must be resolved as quickly as possible, but if the problem is difficult handled, the teacher will call the parents involved in the bullying case. As for the scholls efforts to aplly sanctions to have an effect on students who violate the points of schools rules, the school also makes posters related to 5S culture to attract students to learn